Principles and Practice of Radiotherapy Techniques in Thoracic Malignancies - Ozyigit, Gokhan; Selek, Ugur; Topkan, Erkan (Springer International Publishing : Imprint: Springer, 2016)
This evidence-based guide on the use of radiotherapy in patients with common malignancies of the lung, esophagus, and thymus will help radiation oncologists to deliver optimal care within a multidisciplinary setting. Detailed information is provided on all aspects, from delineation of tumor volumes and organs at risk based on four-dimensional CT simulation through to the various advanced radiotherapy techniques, including stereotactic ablative radiotherapy (SABR), intensity-modulated radiation therapy (IMRT), tomotherapy, volumetric modulated arc therapy (VMAT), and proton therapy. Contouring, treatment planning, and treatment delivery are documented in a range of everyday cases, with illustrations of slice-by-slice delineations on planning CT images and finalized treatment plans based on detailed acceptance criteria. Numerous practical tips are highlighted, and relevant information is included on surgical techniques and systemic therapies. The book will facilitate decision making in the management of patients with common thoracic malignancies and assist in overcoming the challenges encountered in daily clinical practice.